Penerapan Teknologi Pewarnaan Ecoprinting Kulit Kambing Samak Krom pada Usaha Kecil Kerajinan Produk Barang Kulit di Desa Bululawang: Application of Leather Ecoprinting Coloring Technology Samak Krom on Small Businesses Craft leather goods products in Bululawang Village - Wehandaka Pancapalaga; Muhammad Khoirul Fuddin; Radityo Widiatmojo; Rinaldy Achmad Roberth Fathoni; Rini Pebri Utari; Tutik Sulistyowati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Bululawang Village is a village located in Malang Regency, which is an area that has the potential for the leather goods industry. The prospect of the leather goods craft industry provides vast employment opportunities for job seekers in the SME sector and can support Bululawang's becoming a tourist village. In supporting the realization of a tourist village, one of the activities is fostering SMEs, which will later contribute to tourism. One of the SMEs with local potential to be developed is an eco print leathercraft. This can be created because there are many flower plants in the area. Leaves and flowers in Bululawang Village have not been used optimally. The various leaves and flowers contain pigments that can still be used as eco print coloring on tanned leather. Ecoprint leather products can create garments, shoes, and jackets, especially for fashion. This Community Service aims to improve the knowledge and skills of leather SMEs related to the application of goatskin eco print coloring technology. The service method used is education, training, and mentoring. Instruction is given to increase knowledge of eco print on leather. The training was provided to improve skills in making eco print coloring methods on leather. While assistance for those who are interested in business.